Entropy generation in radiative flow of Ree-Eyring fluid due to due rotating disks. Issue 6 (3rd June 2019) - Khan, Muhammad Ijaz; Ahmad Khan, Sohail; Hayat, Tasawar; Faisal Javed, Muhammad; Alsaedi, Ahmed
Abstract : Purpose: This study aims to examine the flow characteristics of Ree–Eyring fluid between two rotating disks. The characteristics of heat transfer are discussed in presence of viscous dissipation, heat source/sink and nonlinear radiative heat flux. Design/methodology/approach: Nonlinear flow expressions lead to ordinary ones through adequate similarity transformations. The ordinary differential system has been tackled through optimal homotopic method. The impact of different flow variables on the velocity field, entropy generation rate and temperature fields is graphically discussed. The surface drag force and heat transfer rate are numerically examined via various pertinent parameters. Findings: By minimization of values of stretching parameter and Brinkman number, the entropy generation rate can be controlled. The entropy generation rate enhances for higher values of magnetic parameter, while the Bejan number is decreased via magnetic parameter. Originality/value: No such work is yet published in the literature.